2011
DOI: 10.1177/0146167211405994
|View full text |Cite
|
Sign up to set email alerts
|

Highlighting Relatedness Promotes Prosocial Motives and Behavior

Abstract: According to self-determination theory, people have three basic psychological needs: relatedness, competence, and autonomy. Of these, the authors reasoned that relatedness need satisfaction is particularly important for promoting prosocial behavior because of the increased sense of connectedness to others that this engenders. In Experiment 1, the authors manipulated relatedness, autonomy, competence, or gave participants a neutral task, and found that highlighting relatedness led to higher interest in voluntee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
143
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(161 citation statements)
references
References 56 publications
9
143
0
2
Order By: Relevance
“…Overall, these results were consistent with the BPNT and SDT literatures with respect to need satisfaction and positive psychological outcomes (e.g., Adie et al, 2012;Gagné et al, 2003;Kipp & Weiss, 2013;McDavid et al, 2014;Molix & Nichols, 2013;Pavey et al, 2011).…”
Section: Psychological Needs and Prosocial Behaviorsupporting
confidence: 89%
See 1 more Smart Citation
“…Overall, these results were consistent with the BPNT and SDT literatures with respect to need satisfaction and positive psychological outcomes (e.g., Adie et al, 2012;Gagné et al, 2003;Kipp & Weiss, 2013;McDavid et al, 2014;Molix & Nichols, 2013;Pavey et al, 2011).…”
Section: Psychological Needs and Prosocial Behaviorsupporting
confidence: 89%
“…Given that the basic need for relatedness has previously been regarded as less important than the other needs , our finding that relatedness was an important mediator in the relationship between motivational climate and prosocial behavior was notable. Indeed, this finding supported recent research indicating that relatedness predicts prosocial behavior (i.e., volunteering and charitable donations; Pavey, Greitemeyer, & Sparks, 2011), and that sport is a context in which relatedness emerges as a significant predictor of well-being over time (Adie et al, 2012;Gunnell et al, 2013). Since relatedness focuses on caring about others (and being cared for oneself), this basic need should logically have a strong relationship with prosocial behaviors which are characterized by an altruistic concern for the welfare of others.…”
Section: Contextual Climates and Anti/prosocial Behaviorsupporting
confidence: 82%
“…Propensity to help was measured using a widely used four-item measure of intention to help (sample item: "I intend to lend my notes to my colleague") (Pavey, Greitemeyer, & Sparks, 2011;Perugini, Conner, & O'Gorman, 2011;Pilati et al, 2008;Rabelo, Hees, & Pilati, 2012;Saslow et al, 2013;Weiner, 1980b), participants indicated their agreement with items using a seven-point Likert scale; in this study the scale showed acceptable internal consistency (α = 0.82).…”
Section: Measures and Proceduresmentioning
confidence: 80%
“…Priming participants to experience a desired meta-motivational state allows the researchers to manipulate participants' current meta-motivational state rather than relying on the T/PSI as a point of comparison. Writing tasks have been used successfully to prime emotions in previous studies, for example, Pavey, Greitemeyer, and Sparks (2011) primed participants into a relatedness state, whilst Hudson and Day (2012) used an expressive writing task to enable participants to recreate and switch between the different metamotivational states.…”
Section: Study 1 Discussionmentioning
confidence: 99%